1998
DOI: 10.1016/s0741-5214(98)70324-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk factor for abdominal aortic aneurysm: HLA-DR2(15), A Japanese study

Abstract: The data suggest that HLA-DR2(15) has an important role as a genetic risk factor for AAA in Japanese patients, as previously reported in a mixed North American population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 9 publications
3
23
0
1
Order By: Relevance
“…An association of HLA-DRB1 alleles (HLA-DR2*15 and *16, *12 and *13) was described by Tilson et al 57 and Rasmussen et al (HLA-DRB1*04 and *15). 58 The presence of the DR␤Gln(70) residue was identified as a risk factor for AAA.…”
Section: Association Of Hla Alleles With Aaamentioning
confidence: 79%
“…An association of HLA-DRB1 alleles (HLA-DR2*15 and *16, *12 and *13) was described by Tilson et al 57 and Rasmussen et al (HLA-DRB1*04 and *15). 58 The presence of the DR␤Gln(70) residue was identified as a risk factor for AAA.…”
Section: Association Of Hla Alleles With Aaamentioning
confidence: 79%
“…These findings were supported by Monux whose results did not reach statistical significance, but suggested HLA-DR B 1 *01 to be protective and HLA-DR Bl*04 to predispose to AAA (Monux 2003). Increased frequency of the HLA-DR2(15) allele has also been described amongst aneurysm patients compared with controls (58.7% vs 28%) in a Japanese population (Hirose 1998).…”
Section: Nitric Oxide Synthasementioning
confidence: 84%
“…In a Japanese population, an increased frequency of the HLA-DR2(15) allele has been demonstrated in aneurysm patients. Other studies have shown HLA-DR B1*02 and B1*04 subtypes as well as HLA-A2 and HLA-B61 antigens to be more common in AAA patients (Rasmussen et al, 2002;Monux et al, 2003;Hirose et al, 1998). Despite this, a more recent study of 241 AAA patients failed to demonstrate a risk association between AAA and these alleles suggesting that the role of these particular genes and the autoimmune component in AAA etiology does not appear to be as crucial as previously proposed (Badger et al, 2007).…”
Section: Human Leukocyte Antigen Genesmentioning
confidence: 84%